(untitled) - Roy Meador (Chelsea, Michigan, 1991)
The book discusses such essential topics as the elements of a proposal, getting ready to write the proposal, using a computer to make your task easier, and preparing a proposal as a team. The book also addresses how to prepare proposals for specific purposes, such as government or foundation grants, venture capital, and intracompany deals. The book will be invaluable to anyone seeking to tap into available grants
Keywords: proposal writing in business,proposal writing in research